2010
DOI: 10.1088/0004-637x/723/1/40
|View full text |Cite
|
Sign up to set email alerts
|

The Resolved Near-Infrared Extragalactic Background

Abstract: We present a current best estimate of the integrated near-infrared (NIR) extragalactic background light (EBL) attributable to resolved galaxies (Integrated Galaxy Light, IGL) in J, H, and K s . Our results for measurements of νI ν in units of nW m −2 sr −1 are 11.7 +5.6 −2.6 in J, 11.5 +4.5 −1.5 in H, and 10.0We derive these new limits by combining our deep wide-field NIR photometry from five widely separated fields with other studies from the literature to create a galaxy counts sample that is highly complete… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
100
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(109 citation statements)
references
References 37 publications
9
100
0
Order By: Relevance
“…The validity of the ×1.2 scaled model at fainter magnitudes than 17 mag was checked using deep star counts complete to AB=20 mag in J-band towards Bootes and NEP with NEWFIRM (Gonzalez et al 2010) and WIRCam/CFHT (Oi et al 2014), respectively. The raw source counts (including galaxies) towards Bootes are compared with the model star counts and also with well-established galaxy count data (Keenan et al 2010) as shown in Figure 8.…”
Section: Integrated Star Lightmentioning
confidence: 99%
“…The validity of the ×1.2 scaled model at fainter magnitudes than 17 mag was checked using deep star counts complete to AB=20 mag in J-band towards Bootes and NEP with NEWFIRM (Gonzalez et al 2010) and WIRCam/CFHT (Oi et al 2014), respectively. The raw source counts (including galaxies) towards Bootes are compared with the model star counts and also with well-established galaxy count data (Keenan et al 2010) as shown in Figure 8.…”
Section: Integrated Star Lightmentioning
confidence: 99%
“…2 suggests that the EBL coming from galaxies is already well constrained in the region from the UV up to the mid-IR but not in the far-IR. Galaxy counts from very deep surveys taken with very sensitive instruments [3,4,5] should be considered as a good estimation of the true EBL from galaxies. On the other hand, different fully independent modelings based on different galaxy data sets [7,9,12] agree in the specific intensity level of the EBL.…”
Section: Extragalactic Background Lightmentioning
confidence: 99%
“…This is mainly due to the contribution of zodiacal light, some orders of magnitude larger than the EBL (e.g., [1,2]). Other observational approaches set reliable lower limits on the EBL, such as measuring the integrated light from discrete extragalactic sources (e.g., [3,4,5]). On the other hand, there are phenomenological approaches in the literature that predict an overall EBL model (i.e., between 0.1 and 1000 µm and for any redshift).…”
Section: Introductionmentioning
confidence: 99%
“…Previous measurements of the EBL have been of two types: direct measurements (e.g., Puget et al 1996;Fixsen et al 1998;Hauser et al 1998;Lagache et al 1999;Cambrésy et al 2001;Bernstein et al 2002;Matsumoto et al 2005Matsumoto et al , 2011Dole et al 2006;Bernstein 2007) and integrated galaxy counts (e.g., Madau & Pozzetti 2000;Totani et al 2001;Xu et al 2005;Dole et al 2006;Hopwood et al 2010;Keenan et al 2010;Berta et al 2011;Béthermin et al 2012). These two methods should converge if the EBL is predominantly derived from galaxies (including any AGN component) and if the photometric data used to detect these galaxies are sufficiently deep.…”
Section: Introductionmentioning
confidence: 99%
“…The remaining discrepancy can be readily reconciled from extrapolations of the source counts, plus some additional contribution from lensed systems (Wardlow et al 2013). In the optical and near IR the situation is less clear, with many direct estimates being a factor of five or more greater than the integrated galaxy counts (see for example the discussion on the near-IR background excess in Keenan et al 2010or Matsumoto et al 2015, despite the advent of very wide and deep data. Either the integrated source counts are missing a significant quantity of the EBL in a diffuse component or the direct measures are overestimated (i.e., the backgrounds are underestimated).…”
Section: Introductionmentioning
confidence: 99%